(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: The antimicrobial sensitivity pattern of organisms is changing rapidly over a short period which is varying from country to country, one place to another, and from one institute to another. Therefore, periodic evaluation of sensitivity patterns is essential for the rational and appropriate use of antibiotics in Pediatric Intensive Care Unit (PICU) settings. This study aimed to see the bacteriological profile and antibiotic sensitivity among the patients with positive blood culture admitted to the PICU of Chittagong Medical College Hospital (CMCH). Materials and methods: All blood culture samples sent from patients hospitalized in the PICU of CMCH between October 2021 and March 2022, were evaluated retrospectively. Information collected includes the demographic data, Primary diagnosis, causative agent and sensitivity pattern of the isolated organisms. Results: Out of 214 blood culture samples growth was found in 29 (13.6%) samples, female (58.6%) higher than male in distribution gender, with median age of 9 months and primary diseases distribution was dominated with pneumonia (65.5%). The most common Gram-Positive Bacteria (GPB) was Coagulase-Negative Staphylococcus (CoNS) (27.9%), followed by Staphylococcus aureus (10.3%). The most common Gram-Negative Bacteria (GNB) was Klebsiella pneumoniae (13.8%), followed by Burkholderiacepacia (10.3%), Escherichia coli (6.9%), Pseudomonas aeruginosa (6.9%) and Acinetobacter baumannii (6.9%). The resistance rates of Coagulasenegative staphylococcus and S. aureus against Ampicillin were 62.5% and 66.7% respectively. The resistance rates of these two organisms to Gentamycin were 50% and 66.7% respectively. Identified GNB were also highly resistant to third generation cephalosporins with a cumulative resistance rate against Ceftriaxone and Cefixime being 50% for each and showed better susceptibility patterns for colistin and levofloxacin. Klebsiella species and E. coli showed better sensitivity to Imipenem and Ciprofloxacin. Klebsiella species were also highly sensitive andBurkholderiacepacia were highly resistant against Gentamycin. Conclusion: The present study contributes information on the prevalence and antibiotic sensitivity of microorganisms in blood culture and use appropriate antibiotic considering the blood culture and sensitivity pattern. JCMCTA 2022 ; 33 (2) : 37-42